Preparation method and application of titanium-niobium-oxygen in-situ doped porous carbon material

The in-situ growth of titanium niobium oxide nanocrystals on a porous carbon substrate via a solvothermal method solved the problem of uniform composite formation of titanium niobium oxide and carbon materials, constructed a stable three-dimensional conductive network, and improved the negative electrode performance of lithium-ion hybrid capacitors.

CN121493978APending Publication Date: 2026-02-10CHINA DATANG GRP TECH INNOVATION CO LTD +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202511602550.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-04
Publication Date
2026-02-10

AI Technical Summary

Technical Problem

Existing technologies make it difficult to achieve uniform composite of titanium niobium oxide and carbon materials at the nanoscale, resulting in high interfacial resistance, blockage of lithium-ion transport channels, and failure of conductive networks, which limits high-rate charge-discharge performance and cycle life.

Method used

Titanium-niobium-oxygen nanocrystals were grown in situ on a porous carbon substrate using a solvothermal method to form a chemically bonded composite material, thereby constructing a robust three-dimensional conductive network and fast ion channels.

Benefits of technology

It significantly improves the electronic conductivity and ion migration rate of the material, achieving high capacity, high rate capability and long cycle life of the anode, and the preparation process is simple and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121493978A_ABST
    Figure CN121493978A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a titanium-niobium-oxygen in-situ doped porous carbon material, and the method comprises the following steps: 1, dispersing a titanium source, a niobium source and a porous carbon substrate in an organic solvent, and stirring to form a uniform precursor suspension; step 2, performing solvothermal reaction on the precursor suspension to enable titanium-niobium-oxygen crystals to perform in-situ nucleation and growth on the surface of the porous carbon substrate and in pores to obtain a composite material precursor; and 3, carrying out high-temperature crystallization treatment on the composite material precursor under the protection of an inert atmosphere to obtain the crystalline titanium-niobium-oxygen in-situ doped porous carbon material. When the composite material is used as a negative electrode of a lithium ion hybrid capacitor, the specific capacities at 0.1 C and 50 C multiplying powers respectively reach 278.9 mAh / g and 133.5 mAh / g, excellent multiplying power performance and cycling stability are shown, the preparation process is simple, the cost is low, and the composite material is suitable for the field of high-performance energy storage devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical energy storage materials and nanocomposite materials technology, and relates to a method for preparing porous carbon materials, specifically a method for in-situ preparation of titanium-niobium-oxygen / porous carbon composite materials for the negative electrode of high-performance lithium-ion hybrid capacitors. Background Technology

[0002] With the increasing demand for fast charging and discharging from electric vehicles, large-scale energy storage, and portable electronic devices, the development of "dual-high" electrochemical energy storage devices that combine high energy density and high power density has become a research hotspot. Hybrid capacitors combine the high energy density of battery-type electrodes with the high power characteristics of capacitor-type electrodes, and are one of the effective ways to meet this demand. Their performance largely depends on the lithium storage capacity and reaction kinetics of the anode material.

[0003] Among numerous anode materials, niobium-based oxides, especially titanium niobium oxides (such as TiNb2O7), stand out due to their high theoretical specific capacity (~387 mAh g⁻¹). -1 ), a safe operating voltage platform (approximately 1.6 V vs. Li), + Lithium oxide (Li₂ / Li₃) and its excellent structural stability make it an ideal candidate anode material for next-generation high-power lithium-ion batteries and hybrid capacitors. However, these materials have extremely low intrinsic electronic conductivity and slow bulk diffusion kinetics of lithium ions within their crystal lattice, which severely limits their capacity utilization and cycle life under high-rate charge-discharge conditions, becoming a bottleneck for their large-scale application in "high-power and high-cycle" energy storage devices.

[0004] To overcome the aforementioned shortcomings, existing technologies generally employ a strategy of compositing titanium niobium oxide with highly conductive carbon materials (such as graphene, carbon nanotubes, and carbon black). These methods mainly include simple physical-mechanical mixing or non-in-situ surface coating. However, these traditional composite methods have significant drawbacks: First, physical mixing makes it difficult to achieve tight and uniform interfacial contact between the carbon material and oxide particles, resulting in high interfacial resistance. Furthermore, during long-term cyclic charging and discharging, the two materials are prone to separation due to volume changes, leading to the failure of the conductive network. Second, non-in-situ carbon coating layers can easily partially block lithium-ion transport channels and are difficult to construct a continuous three-dimensional ion / electron transport network, resulting in limited improvement in rate performance. In addition, the multi-step and complex composite process increases the preparation cost and process uncertainty, which is not conducive to the large-scale and controllable production of materials.

[0005] Therefore, developing a simple and controllable preparation method that can achieve uniform composite formation of titanium niobium oxide and carbon matrix at the nanoscale, forming a stable chemical bond and a three-dimensional conductive network, while also possessing fast ion channels, is of great practical significance for promoting the practical application of high-performance hybrid capacitors. Summary of the Invention

[0006] To address the technical challenges of low electronic conductivity and slow ion diffusion kinetics in niobium-based oxide anode materials, this invention provides a simple and low-cost method for preparing in-situ doped porous carbon materials of titanium-niobium-oxygen and its applications. This method involves the in-situ growth of titanium-niobium-oxygen nanocrystals on a porous carbon substrate via a solvothermal process, forming a chemically bonded, structurally integrated composite material that significantly improves the material's electronic conductivity, ion migration rate, and structural stability. When used as the anode of a lithium-ion hybrid capacitor, this composite material exhibits specific capacities of 278.9 mAh / g and 133.5 mAh / g at 0.1C and 50C rates, respectively, demonstrating excellent rate performance and cycle stability. Furthermore, the preparation process is simple and low-cost, making it suitable for high-performance energy storage devices.

[0007] The objective of this invention is achieved through the following technical solution:

[0008] A method for preparing titanium-niobium-oxygen in-situ doped porous carbon material includes the following steps:

[0009] Step 1: Preparation of the precursor suspension: Titanium source, niobium source, and porous carbon substrate are co-dispersed in an organic solvent and stirred to form a homogeneous precursor suspension. The molar ratio of the titanium source to the niobium source is 1:2 to match the ideal stoichiometric ratio of TiNb₂O₇. The porous carbon substrate accounts for 5-20% of the total mass of the titanium and niobium sources, preferably 8-15%. The porous carbon substrate is graphitized porous carbon prepared from coal as a precursor through pre-carbonization and potassium-based activation, with a specific surface area of ​​1500-3000 m². 2 / g, pore volume 1.0~2.0 cm³ 3 / g; the titanium source is tetrabutyl titanate, titanium sulfate or isopropyl titanate, preferably tetrabutyl titanate; the niobium source is niobium pentachloride, niobium oxalate or niobium ethanol, preferably niobium pentachloride; the organic solvent is ethanol, ethylene glycol or isopropanol, preferably anhydrous ethanol;

[0010] Step 2, Solvothermal reaction: The precursor suspension is subjected to a solvothermal reaction to allow titanium niobium oxide crystals to nucleate and grow in situ on the surface and within the pores of a porous carbon substrate, thereby obtaining a composite material precursor. The temperature of the solvothermal reaction is 150~200 ℃, preferably 170~190 ℃, and the time is 12~36 hours, preferably 18~30 hours.

[0011] Step 3: High-temperature crystallization treatment: The composite material precursor is subjected to high-temperature crystallization treatment under an inert atmosphere to obtain crystalline titanium-niobium-oxygen in-situ doped porous carbon material, wherein: the inert atmosphere is argon or nitrogen, and the gas flow rate is 100~300 mL / min; the heating rate of the high-temperature crystallization treatment is 2~10 ℃ / min, the temperature is 700~900 ℃, preferably 750~850 ℃, and the holding time is 2~6 hours; in the titanium-niobium-oxygen in-situ doped porous carbon material, titanium-niobium-oxygen nanocrystals are uniformly distributed on the surface and in the pores of the porous carbon substrate, and are tightly bonded to the porous carbon substrate through chemical bonding.

[0012] Compared with the prior art, the present invention has the following advantages:

[0013] 1. This invention uses coal-based graphitized porous carbon (GPC) prepared through high-temperature pre-carbonization and potassium-based activation as the cathode material. This material combines high specific surface area, well-developed hierarchical channels, and a highly graphitized carbon framework, providing abundant double-layer energy storage sites. Its stable graphitized structure significantly improves the conductivity and structural stability of the electrode, thereby ensuring the excellent long cycle life of the hybrid capacitor.

[0014] 2. This invention successfully constructed a composite anode material (TNO@GPC) with uniformly grown titanium niobium oxide (TNO) nanocrystals on a GPC substrate through an in-situ composite strategy. The GPC substrate provides TNO with a stable three-dimensional conductive network and fast ion transport channels, effectively overcoming the inherent low conductivity and slow ion diffusion kinetics of niobium-based oxides, and greatly improving the rate performance and reversible capacity of the anode. Attached Figure Description

[0015] Figure 1 This is a scanning electron microscope (SEM) image of the titanium niobium oxygen in-situ doped porous carbon material (TNO@GPC) prepared in Example 1;

[0016] Figure 2 These are transmission electron microscope (TEM) images of TNO@GPC prepared in Example 1;

[0017] Figure 3 The X-ray diffraction (XRD) pattern of TNO@GPC prepared in Example 1 is shown.

[0018] Figure 4 This is the Raman spectrum of TNO@GPC prepared in Example 1;

[0019] Figure 5 The cyclic voltammetry (CV) curves of the half-cell with TNO@GPC as the negative electrode prepared in Example 1 are shown.

[0020] Figure 6The graph shows the rate performance of the half-cells prepared in Example 1 using TNO@GPC and pure-phase TNO as the negative electrode. Detailed Implementation

[0021] The technical solution of the present invention will be further described below with reference to the accompanying drawings, but it is not limited thereto. Any modifications or equivalent substitutions to the technical solution of the present invention that do not depart from the spirit and scope of the technical solution of the present invention should be covered within the protection scope of the present invention.

[0022] Example 1

[0023] Preparation of porous carbon substrate (GPC): Xinjiang Zhundong coal was used as a precursor and pre-carbonized at 700℃ under a nitrogen atmosphere for 1 hour. Subsequently, the pre-carbonized product was mixed with KOH at a mass ratio of 1:3 and activated at 900℃ for 1 hour. The product was washed with hydrochloric acid, hydrofluoric acid, and deionized water until neutral and then dried to obtain graphitized porous carbon (GPC).

[0024] Preparation of in-situ titanium-niobium-oxygen doped porous carbon material (TNO@GPC):

[0025] a. Weigh 2.5 mmol of tetrabutyl titanate and 5 mmol of niobium pentachloride, and add them together with 60 mg of the GPC prepared above (accounting for 10 wt% of the total mass of the titanium-niobium source) into 60 mL of anhydrous ethanol. Stir magnetically for 60 minutes to form a uniform suspension.

[0026] b. Transfer the suspension to a 100 mL polytetrafluoroethylene-lined high-pressure reactor, seal it, and place it in an oven at 180 °C for 24 hours.

[0027] c. After the reaction is complete, allow the mixture to cool naturally to room temperature. Collect the precipitate by centrifugation and wash it several times with ethanol to obtain the composite material precursor.

[0028] d. Place the precursor in a tube furnace and heat it to 800 °C at a rate of 5 °C / min under an argon atmosphere (flow rate 200 mL / min), and hold it at that temperature for 5 hours.

[0029] e. After cooling to room temperature in the furnace, remove the sample and dry it overnight at 80 °C to obtain the final product TNO@GPC.

[0030] Example 2

[0031] Preparation of porous carbon substrate (GPC): Same as in Example 1.

[0032] Preparation of in-situ titanium-niobium-oxygen doped porous carbon material (TNO@GPC):

[0033] a. Weigh 2.5 mmol of isopropyl titanate and 5 mmol of niobium oxalate, and add them together with 45 mg of the GPC prepared above (accounting for 7.5 wt% of the total mass of the titanium-niobium source) into 60 mL of ethylene glycol. Stir magnetically for 90 minutes to form a uniform suspension.

[0034] b. Transfer the suspension to a 100 mL high-pressure reactor lined with polytetrafluoroethylene, seal it, and place it in an oven at 190°C for 20 hours.

[0035] c. After the reaction is complete, allow the mixture to cool naturally to room temperature. Collect the precipitate by centrifugation and wash it several times with ethanol to obtain the composite material precursor.

[0036] d. Place the precursor in a tube furnace and heat it to 750 °C at a rate of 3 °C / min under a nitrogen atmosphere (flow rate 150 mL / min), and hold it at that temperature for 6 hours.

[0037] e. After cooling to room temperature in the furnace, remove the sample and dry it overnight at 80 °C to obtain the final product TNO@GPC.

[0038] Comparative Example 1:

[0039] Pure-phase TNO materials were prepared according to the method of Example 1, but without the addition of GPC.

[0040] Material characterization:

[0041] The material obtained in Example 1 was characterized. Figure 1 and Figure 2 SEM and TEM images show that titanium niobium oxide nanospheres (approximately tens to hundreds of nanometers in size) are uniformly attached to the surface and interior of the porous framework of GPC. Figure 3 The XRD pattern confirmed that the obtained crystal was pure phase TiNb2O7, and the diffraction peak intensity decreased after recombination, indicating that the presence of GPC refined the grains. Figure 4 The intensity ratio (ID / IG) of the D peak to the G peak in the Raman spectrum is 0.52, indicating that there are abundant defects in the carbon matrix of the composite material, which is beneficial to electrochemical activity.

[0042] Electrochemical performance testing:

[0043] The materials obtained in Example 1 and Comparative Example 1 were used as negative electrode active materials, mixed with conductive carbon black and binder in a ratio of 8:1:1 to form a slurry, which was then coated onto copper foil to prepare an electrode sheet. A CR2032 coin cell was assembled and tested in an argon glove box using lithium metal as the counter electrode.

[0044] The materials obtained in Examples 1, 2, and Comparative Example 1 were characterized and subjected to electrochemical tests. The results showed that the TNO@GPC composite materials prepared in Examples 1 and 2 exhibited superior crystal structure, porosity, and electrochemical performance compared to the pure-phase TNO in Comparative Example 1. Specifically, the material in Example 1 had a discharge specific capacity of 133.5 mAh g⁻¹ at 50 C. -1 The material in Example 2 also exhibited similar high-rate performance (e.g., 125 mAh g⁻¹). -1 (above), significantly higher than the 72.5 mAh g of pure TNO in Comparative Example 1. -1 This fully demonstrates that the present invention can effectively improve the electrochemical performance of titanium-niobium oxide materials under different preferred process parameters.

[0045] This invention successfully prepared a high-performance titanium-niobium-oxygen / porous carbon composite material by using a simple in-situ solvothermal-thermal treatment method and by adjusting parameters such as carbon content, reaction temperature, and time. When used as the negative electrode of a lithium-ion hybrid capacitor, this material exhibits excellent characteristics such as high capacity, high rate capability, and long cycle life, and has a wide process window and good repeatability.

Claims

1. A method for preparing titanium-niobium-oxygen in-situ doped porous carbon material, characterized in that... The method includes the following steps: Step 1: Preparation of precursor suspension: Titanium source, niobium source, and porous carbon substrate are co-dispersed in an organic solvent and stirred to form a homogeneous precursor suspension, wherein: the molar ratio of titanium source to niobium source is 1:2; and the mass of the porous carbon substrate accounts for 5-20% of the total mass of titanium source and niobium source. Step 2, Solvothermal reaction: The precursor suspension is subjected to a solvothermal reaction to allow titanium niobium oxide crystals to nucleate and grow in situ on the surface and within the pores of a porous carbon substrate, thereby obtaining a composite material precursor. The temperature of the solvothermal reaction is 150~200 ℃ and the time is 12~36 hours. Step 3, High-temperature crystallization treatment: The composite material precursor is subjected to high-temperature crystallization treatment under inert atmosphere protection to obtain crystalline titanium niobium oxygen in-situ doped porous carbon material, wherein: the temperature of the high-temperature crystallization treatment is 700~900 ℃, and the holding time is 2~6 hours.

2. The method for preparing titanium-niobium-oxygen in-situ doped porous carbon material according to claim 1, characterized in that... The porous carbon substrate accounts for 8-15% of the total mass of the titanium and niobium sources.

3. The method for preparing titanium-niobium-oxygen in-situ doped porous carbon material according to claim 1, characterized in that... The porous carbon substrate is a graphitized porous carbon prepared from coal as a precursor through pre-carbonization and potassium-based activation, with a specific surface area of ​​1500~3000 m². 2 / g, pore volume 1.0~2.0 cm³ 3 / g; the titanium source is tetrabutyl titanate, titanium sulfate or isopropyl titanate; the niobium source is niobium pentachloride, niobium oxalate or niobium ethanol; the organic solvent is ethanol, ethylene glycol or isopropanol.

4. The method for preparing titanium-niobium-oxygen in-situ doped porous carbon material according to claim 3, characterized in that... The titanium source is tetrabutyl titanate; the niobium source is niobium pentachloride; and the organic solvent is anhydrous ethanol.

5. The method for preparing titanium-niobium-oxygen in-situ doped porous carbon material according to claim 1, characterized in that... The solvothermal reaction is carried out at a temperature of 170-190 °C for 18-30 hours.

6. The method for preparing titanium-niobium-oxygen in-situ doped porous carbon material according to claim 1, characterized in that... The inert atmosphere is argon or nitrogen, and the gas flow rate is 100~300 mL / min.

7. The method for preparing titanium-niobium-oxygen in-situ doped porous carbon material according to claim 1, characterized in that... The heating rate of the high-temperature crystallization treatment is 2~10℃ / min.

8. The method for preparing titanium-niobium-oxygen in-situ doped porous carbon material according to claim 1, characterized in that... The high-temperature crystallization treatment is performed at a temperature of 750~850 ℃.

9. A titanium-niobium-oxygen in-situ doped porous carbon material prepared by the method of any one of claims 1-8.

10. The application of a titanium-niobium-oxygen in-situ doped porous carbon material prepared by the method of any one of claims 1-8 in the negative electrode of a lithium-ion hybrid capacitor.

Citation Information

Patent Citations

  • Method for preparing titanium niobate and carbon nanotube composite material and lithium ion capacitor with material as negative electrode

    CN104538207A

  • Preparation method of carbon modified titanium niobate material, carbon modified titanium niobate material, and lithium ion capacitor and negative electrode paste thereof

    CN108183039A

  • Carbon / titanium niobium oxide composite negative electrode material and preparation and application thereof

    CN109859957A

  • One-step cooperative development method of graphite microcrystals and pores in anthracite-based porous carbon

    CN110330016A

  • Preparation method of low-rank coal-based porous carbon and application of low-rank coal-based porous carbon in supercapacitor

    CN111710530A